Effects of 16-weeks of strength training on jump height and anthropometric variables in U19 semi-professional male soccer players - González-Fernández, Francisco Tomás (2023)
Purpose: The aim of our study was to examine the effect of 16 weeks of strength training on anthropometric characteristics and jump height in semi-professional male players after a pre-season period. Methods: A parallel two-group, longitudinal (pre, post) design was used with physical tests performed before (preintervention) and after (postintervention) the 16-week intervention period. The soccer players were assigned and matched into two groups, an experimental group (EG) and a control group (CG), based on the team of which they were a part. Results: A two-way ANOVA was performed with group and time as factors. The results of a two-way ANOVA revealed no time×group interaction for body composition or jump height. Nevertheless, a paired measures t-test of weight, fat mass, lean mass, and countermovement jump (CMJ) test metrics (pre-post) and group (CG and EG) showed an improvement in all measures (p<0.01). Discussion: The 16-week intervention program resulted in an improvement in the EG both at the level of body composition and in CMJ performance. Conclusions: Despite the benefits of the 16-week intervention program, a combination of training methods that includes power, agility-coordination, speed, and strength can enhance such improvements. It is important to take this strength-specific capacity into account in training, due to the importance outlined in the sport of soccer both for its transfer to both linear and COD sprints and specific strength skills and mainly to vertical jump.